\(\displaystyle\frac{{2}}{{3}}{\left({4}{x}-{5}\right)}={8}\)

\(\displaystyle{\left(\frac{{8}}{{3}}\right)}{x}-\frac{{10}}{{3}}=\frac{{24}}{{3}}\)

\(\displaystyle{8}{x}-{10}={24}\)

\(\displaystyle{8}{x}={34}\)

\(\displaystyle{x}=\frac{{34}}{{8}}\)

\(\displaystyle{x}={4}\frac{{2}}{{8}}={4}\frac{{1}}{{4}}\)

\(\displaystyle{\left(\frac{{8}}{{3}}\right)}{x}-\frac{{10}}{{3}}=\frac{{24}}{{3}}\)

\(\displaystyle{8}{x}-{10}={24}\)

\(\displaystyle{8}{x}={34}\)

\(\displaystyle{x}=\frac{{34}}{{8}}\)

\(\displaystyle{x}={4}\frac{{2}}{{8}}={4}\frac{{1}}{{4}}\)